The Effectiveness of Restorative Justice in Resolving Minor Crimes at the Police Level: A Comparative Study Between Formal Legal Approach and Restorative Justice - Flora, Henny Saida; Hajriana, Hajriana; Dwiprigitaningtias, Indah; Suningrat, Nining; Zuwanda, Zulkham Sadat; Puspitasari, Dyah Rosiana (PT Inovasi Pratama Internasional, 2025)
This study examines how restorative justice (RJ) and formal legal procedures compare in handling minor crimes at the police level in Jakarta, Indonesia. Using a qualitative legal-methods approach, it analyzes Indonesian laws and regulations (KUHP, KUHAP, Perkapolri, etc.), official police data, and recent case studies (2021–2025) from Jakarta police divisions. Key findings indicate that, under Perkapolri No. 8/2021 and Law No. 8/2021 (amending KUHAP), Indonesian police can now resolve many non-violent minor offenses via RJ. For example, Polres Metro Jakarta Barat reported resolving 525 cases through RJ in 2022. Compared to formal prosecution (which proceeds to court and possible imprisonment), RJ often brings faster, amicable settlements and reduces case backlogs. However, strict criteria apply: RJ is limited to relatively minor crimes with victim consent, and excluded are serious offenses or those injuring public justice. An illustrative case in South Jakarta involved a laptop theft on public transit resolved by RJ after the victim reclaimed her property and withdrew charges. This comparative analysis finds that while RJ has effectively resolved many petty cases (with support from police policies and victim participation), formal procedures remain necessary for severe crimes to ensure legal certainty and social justice. The study concludes that Indonesia’s dual approach—relying on formal law for serious offenses and RJ for minor disputes—offers practical benefits, provided safeguards (e.g. clear guidelines and voluntariness) are maintained.